Horkos [oath] and the sacrament of language – The purloined letter - Meylahn, Johann-Albrecht (HTS teologiese studies, 2013)
The article will bring a reading of Agamben’s interpretation of horkos [oath] in the Sacrament of language, a reading of Derrida’s faith as the grammar of language, into conversation with Lacan’s interpretation of Poe’s ‘The purloined letter’ by taking into consideration the context of this reading: South Africa. South Africa is a multilingual context in the fullest sense of the word ‘multilingual’, and as such, it is faced with the dilemma of a corrupt postal system. The postal system is a metaphor for the system of communication where messages are sent and received. This postal system is corrupt as the sender and receiver of messages are not sacramentally bound by the same oath, and therefore the letters are doomed to be purloined. Derrida’s différance and the grammar of faith transcends the various languages and the various oaths as the quasi-transcendental condition for the sacrament of language, thereby opening a sacred space to encounter the inevitable corruption of the postal service.